Understanding and addressing adult sexual attraction to children a study of paedophiles in contemporary society - Goode, Sarah D. (Routledge : Arts & Humanities Research Council, 2010)
This groundbreaking book explores what can be done to stop paedophilia, seeking a new understanding of it in order to better prevent child sexual abuse and making use of case studies and primary interview-data.